Transmodernidad, vías autóctonas y trabajo independiente para desarrollar proyectos musicales costarricenses - Rojas, José Manuel (2014)
This paper begins proposing a reflection on the rationality of history which is understood by articulating human knowledge and the history of social relations. I propose to explore ways to work with autochthonous and decolonizing musical projects in Costa Rica, independent from institutions. To do so, I analyze the National Theatre, as a symbolic space, our hybrid and heterogeneous cultural background, the organology and dance in Costa Rica and how these elements are influenced by the media. In music, the concept of time and rationality are different in Europe and Latin America: Resistance in Latin American musical culture is shown throughout syncopation. Based on these ideas I expose on the musical project Synthesis, as a challenge to the dictatorship of the musical taste and try to start a musical reflection that leads to an autochthonous musicology, to an epistemic detach.